Modern Business Statistics - Anderson, David R. Williams, Thomas A. and Sweeney, Dennis J. (Australia Thoson, 2006)
This comprehensive introduction to business statistics text balances a conceptual understanding of statistics with the real-world application of statistical methodology. The latest version of Microsoft Excel is integrated throughout the text, showing step-by-step instructions and screen captures to enhance student learning. The authors have been writing market-leading business statistics textbooks for over 20 years, and this new edition contains the same student learning features that have made ASW products best sellers for more than two decades.
Includes Colored Illustrations and index.
Keywords: Microsoft Excel (Computer file)